2020
DOI: 10.1016/s1473-3099(20)30482-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of COVID-19 in 104 people with SARS-CoV-2 infection on the Diamond Princess cruise ship: a retrospective analysis

Abstract: Background The ongoing COVID-19 pandemic is a global threat. Identification of markers for symptom onset and disease progression is a pressing issue. We described the clinical features of people infected on board the Diamond Princess cruise ship who were diagnosed with asymptomatic severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection or mild or severe COVID-19, on admission to the Self-Defense Forces Central Hospital (Tokyo, Japan) and at the end of observation.Methods This retrospective, sin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
212
6
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(241 citation statements)
references
References 20 publications
16
212
6
7
Order By: Relevance
“…These ndings contrast with the ndings of previously published studies of COVID-19. In most study series, fever was the most common symptom, followed by cough (5,13,19). Interestingly, most published studies reported sore throat as a less common symptom, reported only in 13.5% by Guan et al in China, 23.8% by Nitesh Gupta et al in India, whereas in our study sore throat is the most common symptom (5,21).…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…These ndings contrast with the ndings of previously published studies of COVID-19. In most study series, fever was the most common symptom, followed by cough (5,13,19). Interestingly, most published studies reported sore throat as a less common symptom, reported only in 13.5% by Guan et al in China, 23.8% by Nitesh Gupta et al in India, whereas in our study sore throat is the most common symptom (5,21).…”
Section: Discussioncontrasting
confidence: 54%
“…In our study the mean age is 37 years with nearly 50% being otherwise healthy and physically t navy personnel. These young and healthy individuals are more likely to develop asymptomatic infection with less prominent symptoms than older individuals (5,19). Intensive contact tracing and screening helped in recognising more patients with asymptomatic illnesses in our study.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Firstly, pre-hospital kidney function, de ned as renal functional reserve (25), might be critical in renal prognosis with higher creatinine level on hospital admission in patients who will develop AKI (94 mol.l ¹ in AKI group vs 74 mol.l ¹in non-AKI group). This creatinine value depends on patient's prior renal function but also on many other factors: hypovolemia induced by prolonged fever, infection-induced digestive disorders (26) and chronic hypertension, especially if treated by ACE inhibitors (27,28). However, hypovolemia may, at least partly, play a role as up to 50% of SARS-COV-2 patients had modi ed fractional excretion of urea during their ICU stay related to ARDS management, that requires avoidance of excess uid infusion (29).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the leukocyte count indicated that white blood cells have no obvious involvement in, or correlation with, the immune process of the disease; however, it is also possible that the patients in this group are all imported patients with relatively mild illness [12]. Earlier studies have shown that lymphopenia is a typical laboratory abnormality observed during highly pathogenic coronavirus infections [13,14], such as severe acute respiratory syndrome coronavirus (SARS-CoV) and Middle East respiratory syndrome coronavirus (MERS-CoV) infections [15,16]. We observed that the lymphocyte count in the > 65-year-old patients was less than that in the < 40-year-old and 40-65-years-old patients after 7 and 14 days of treatments.…”
Section: Discussionmentioning
confidence: 99%